Investigating complexities and opportunities related to extractivism in Africa - Volmink, Mark (New Agenda: SA Journal of Social and Economic Policy, 2025)
Extractivism in Africa presents a paradox of substantial economic opportunities and significant social, environmental, and political complexities. Africa’s rich natural resources have attracted foreign investment, contributed to economic growth, and improved infrastructure. This paper examined how extractivism has  led to displacement, human rights violations, environmental degradation, and  corruption, perpetuated by neocolonialism. Based on a review of literature this article draws on insights from several sources , including articles and reports and describes concepts and a theoretical framework relevant to extractivism in Africa.  While the findings of this study articulate the challenges and complexities of extractivism, it also  uncovered opportunities that exist for Africa to harness its resources for inclusive growth and sustainable development. This necessitates the enhancement of institutional capacity, promoting transparency and accountability, and ensuring participation in global trade. Regional inter-linkages and improved policies can also maximize benefits and mitigate risks. By addressing the complexities and grasping opportunities, Africa can transform extractivism into a catalyst for equitable and sustainable development.